IgG4- related disease, a case series from Sarawak Malaysia - Lee Kar Hoo, Lee; Wendy Lee Wan Hui, Lee; Benjamin Sachdev Manjit Singh, Sachdev; Cheong Yaw Kiet, Cheong; Ahmad Tirmizi, Jobli; Lee Tung Hiong, Lee; Ling Guo Rey, Ling; Sharifah Aishah, Wan; Teh Cheng Lay, Teh (John Wiley & Sons, 2021)
Background: IgG4- related disease (IgG4- RD) is a novel entity of disease first recognised in 2003. It has wide spectrum of clinical manifestations, virtually affecting any organ. It’s epidemiology remain poorly described and treatment guideline still lacking. Methods: We describe 7 IgG4RD cases diagnosed and treated in 2 hospitals with rheumatologist in Sarawak from 2015 till 2020. Results: 4 males and 3 females were reported with age during diagnosis ranging from 34 to 74 years old. 4 patients had tumefactive lesions (lacrimal gland and salivary gland swelling), 2 had obstructive symptoms (obstructive uropathy due to retroperitoneal fibrosis, obstructive jaundice secondary to autoimmune pancreatitis) and 1 had renal failure and proteinuria as presenting symptoms. Time taken from onset of symptoms to diagnosis range from 8 months to 23 years. In all cases, histopathological findings were the prompt towards diagnosis of IgG4- RD. All patients fulfilled the ACR- EULAR classification criteria whereas only 3 met the 2010 JCR comprehensive diagnostic criteria, due to lack of IgG4 level in others. All patients showed rapid response to steroid therapy, complete resolution of salivary gland swelling were seen in 3 months, stent removal in those with obstructive symptoms were achieved in 6 months whereas resolution of proteinuria was seen in 2 months. All remained in remission currently with or without treatment. Initial dose of prednisolone used ranged from 0.2 to 0.6mg/kg/day, all with good effect. Conclusion: IgG4- RD is indolent but often highly destructive. It is treatable and if diagnosed early, damage is potentially reversible. In terms of diagnosis, we feel that the ACR- EULAR classification criteria is more practical compared to the JCR criteria in places where resources are limited and laboratory testing of serum IgG4 level is not available. Good awareness and high index of suspicion among clinicians, radiologists and pathologists are thus essential in timely diagnosis and prompt treatment of IgG4- RD.